2003
DOI: 10.1051/0004-6361:20031199
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic H+Li and H-+Li+collisions and non-LTE Li I line formation in stellar atmospheres

Abstract: Abstract. Rate coefficients for inelastic collisions between Li and H atoms covering all transitions between the asymptotic states Li(2s,2p,3s,3p,3d,4s,4p,4d,4f)+H(1s) and Li + +H − are presented for the temperature range 2000-8000 K based on recent cross-section calculations. The data are of sufficient completeness for non-LTE modelling of the Li I 670.8 nm and 610.4 nm features in late-type stellar atmospheres. Non-LTE radiative transfer calculations in both 1D and 3D model atmospheres have been carried out … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
152
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(166 citation statements)
references
References 21 publications
13
152
1
Order By: Relevance
“…Thus, the new RM data for electron collisions did not have a strong effect on non-LTE modelling, since the existing data were relatively good; see Osorio et al (2011) for Li, Lind et al (2011) for Na. Data for hydrogen collision processes, including charge transfer, have been calculated for Li by Barklem et al (2003), and for Na by Barklem et al (2010), and used in non-LTE studies by Barklem et al and Lind et al (2009) in the case of Li and Lind et al (2011) for Na. These studies found for both elements that CH processes have practically no effect on the non-LTE modelling, while CH0, in particular that involving the first excited S -state, had a significant effect because it brought this level into closer detailed balance with the continuum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the new RM data for electron collisions did not have a strong effect on non-LTE modelling, since the existing data were relatively good; see Osorio et al (2011) for Li, Lind et al (2011) for Na. Data for hydrogen collision processes, including charge transfer, have been calculated for Li by Barklem et al (2003), and for Na by Barklem et al (2010), and used in non-LTE studies by Barklem et al and Lind et al (2009) in the case of Li and Lind et al (2011) for Na. These studies found for both elements that CH processes have practically no effect on the non-LTE modelling, while CH0, in particular that involving the first excited S -state, had a significant effect because it brought this level into closer detailed balance with the continuum.…”
Section: Discussionmentioning
confidence: 99%
“…We wish to emphasize that with regard to hydrogen collisions in general, the accurate quantum (Barklem et al 2003;Barklem et al 2010Barklem et al , 2012 as well as the more approximate model calculations (Belyaev 2013;Belyaev et al 2014), based on a correct physical background, provide non-zero rate coefficients for both optically allowed and optically forbidden transitions, as well as for charge transfer processes, which generally have the highest rate coefficients among all hydrogen collision processes. Thus, the Drawin formula fails to provide reliable estimates for important inelastic processes in collisions with hydrogen.…”
Section: Hydrogen Atomsmentioning
confidence: 99%
“…Kurucz 1993;Plez 1998;Johansson et al 2003;Lawler et al 2006) and photoionization rates (e.g. Badnell et al 2005) The progress for the important collisional data is less satisfactory in spite of some recent advances (Barklem et al 2003;Barklem 2007a). Non-LTE calculations therefore still normally employ various recipes based on classical physics for electron and hydrogen collisions, often with a scaling factor somehow calibrated.…”
Section: Ingredients For Solar Spectroscopic Analysesmentioning
confidence: 99%
“…It is important to realize that such empirical calibrations of S H is certainly no substitute to having real quantum mechanical or laboratory estimates, since the necessary thermalization may well come from other atomic processes than H collisions, as in the case of charge transfer reactions in Li (Barklem et al 2003). Furthermore, the observations of Allende Prieto et al were not optimal.…”
Section: Caffau Et Al (2008)mentioning
confidence: 99%
“…They are, however, included in this study because (Li + He + ) collision pairs are obtained here via charge transfer processes in (Li + + He) collisions. In addition, even if lithium is rather rare compared to the other primordial elements synthesized in the early Universe, inelastic collisional processes of neutral lithium with hydrogen and other atomic or ionic species are of high interest in modeling stellar atmospheres (Carlsson et al 1994;Barklem et al 2003;.…”
Section: Introductionmentioning
confidence: 99%